Dysphagia in Patients With Severe Coronavirus Disease 2019—Potential Neurologic Etiologies. (22nd January 2021) - Dziewas, Rainer; Hufelschulte, Lisa-Marie; Lepper, Johannes; Sackarnd, Jan; Minnerup, Jens; Teismann, Inga; Ahring, Sigrid; Claus, Inga; Labeit, Bendix; Muhle, Paul; Suntrup-Krüger, Sonja; Warnecke, Tobias; et al.
Abstract : Importance: Dysphagia is a common complication of critical illness, and many known risk factors are also present in critically ill coronavirus disease 2019 victims. Objectives: To investigate dysphagia in patients with severe coronavirus disease 2019. Design, Setting, and Participants: In this case series, we report results of dedicated evaluation of swallowing function in six consecutive, tracheotomized coronavirus disease 2019 patients after they had survived acute respiratory distress syndrome and were weaned from the respirator. Main Outcomes and Measures: Dysphagia was assessed with flexible endoscopic evaluation of swallowing. Results: Three patients suffered from severe dysphagia and airway compromise precluding decannulation, whereas in the other, three swallowing was less critically impaired, and the tracheal cannula could be removed. Four patients presented with additional laryngeal dysfunctions not typically seen in acute respiratory distress syndrome survivors. Conclusion and Relevance: Dysphagia with impaired airway protection is a key feature in coronavirus disease 2019 acute respiratory distress syndrome survivors. Apart from critical illness polyneuropathy, coronavirus disease 2019–related involvement of the peripheral and central nervous system may contribute to swallowing impairment and laryngeal dysfunction.